2011
DOI: 10.3892/ol.2011.544
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutation and methylation influences the outcome of colorectal cancer

Abstract: Abstract. Colorectal cancer (CRC) occurs through the accumulation of genetic and epigenetic alterations. The epigenetic abnormalities, in cooperation with genetic alterations, are capable of causing aberrant gene function that results in cancer. In the present study, we examined mutations and methylation status in 164 CRCs to determine whether the combination of genetic and epigenetic alterations may be used to classify CRC patients in relation to their clinicopathological characteristics and outcomes. Mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
5
22
0
Order By: Relevance
“…Full texts and data integrity were then reviewed and another 249 articles were excluded. Finally, 27 clinical cohort studies were included in this meta-analysis (Liang et al, 1999;Wiencke et al, 1999;Wang et al, 2001;Yi et al, 2001;Hibi et al, 2002;Nakayama et al, 2002;van Rijnsoever et al, 2002;Zou et al, 2002;Cheng et al, 2003;Norrie et al, 2003;Yang et al, 2003;Sanz-Casla et al, 2005;Iacopetta et al, 2006;Ishiguro et al, 2006;Li et al, 2006;Miranda et al, 2006;Krtolica et al, 2007;Mas et al, 2007;Nakayama et al, 2007;Kazama et al, 2008;Wettergren et al, 2008;Goto et al, 2009;Aoyagi et al, 2011;Miladi-Abdennadher et al, 2011;Iida et al, 2012;Sameer et al, 2012;Veganzones-de-Castro et al, 2012). The publication years of the eligible studies ranged from 1999 to 2012.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Full texts and data integrity were then reviewed and another 249 articles were excluded. Finally, 27 clinical cohort studies were included in this meta-analysis (Liang et al, 1999;Wiencke et al, 1999;Wang et al, 2001;Yi et al, 2001;Hibi et al, 2002;Nakayama et al, 2002;van Rijnsoever et al, 2002;Zou et al, 2002;Cheng et al, 2003;Norrie et al, 2003;Yang et al, 2003;Sanz-Casla et al, 2005;Iacopetta et al, 2006;Ishiguro et al, 2006;Li et al, 2006;Miranda et al, 2006;Krtolica et al, 2007;Mas et al, 2007;Nakayama et al, 2007;Kazama et al, 2008;Wettergren et al, 2008;Goto et al, 2009;Aoyagi et al, 2011;Miladi-Abdennadher et al, 2011;Iida et al, 2012;Sameer et al, 2012;Veganzones-de-Castro et al, 2012). The publication years of the eligible studies ranged from 1999 to 2012.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Therefore, it is biologically plausible that genetic mutations of the p16 gene may modulate the development and progression of CRC (Lopes et al, 2008). However, some other studies demonstrated that the relationship between p16 and the development and progression of CRC remains controversial Iida et al, 2012). Therefore, we performed a meta-analysis of all available data to evaluate the relationships between p16 gene promoter methylation and the clinicopathologic features of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…A gain of transformative enzymatic function in both cell lines and orthotopic models results from mutation within both regions [6], [7]. For colorectal carcinoma, the prevalence of PIK3CA mutation was reported to be between 7% and 32%, with G>A transversions in exon 9 being the most commonly observed configuration [4], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…68-82 Studies which used Pyrosequencing assay 60,83,84 (which is more sensitive than Sanger sequencing 85 ) generally show higher frequencies of PIK3CA mutations than Sanger sequencing studies. 61,62,69,80,86 Considering mutations in other less-commonly mutated exons as well as false negativity in molecular assays (particularly, Sanger sequencing), it is estimated that approximately 20% of colorectal cancers in the general population harbor PIK3CA mutations. Interestingly, the prevalence of PIK3CA mutations in colorectal cancer increases continuously from rectum (approximately 10%) to cecum (approximately 25%), 62,87 supporting the “colorectal continuum” paradigm, 88 and an important interplay of gut microbiota and host response.…”
Section: Introduction: Aspirin As Anti-cancer Drugmentioning
confidence: 99%